1992
DOI: 10.3171/jns.1992.77.5.0804
|View full text |Cite
|
Sign up to set email alerts
|

Remote recurrence of craniopharyngioma in the epidural space

Abstract: The case is reported of a 28-year-old man with "ectopic" craniopharyngioma recurring in the epidural space 21 years after the original tumor was resected. Previously described cases of similar remote recurrences as well as some features of the biological behavior of craniopharyngioma are discussed. The rarity of this postoperative complication is addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…Either tumor may be cystic, solid, or both (Burger et al, 1994). Despite their benign histology, craniopharyngiomas may rarely recur as a result of implantation along the operative tract or as remote deposits or metastases due to cerebrospinal uid spread (Barloon et al, 1988;Gupta et al, 1999;Israel and Pomeranz, 1995;Ito et al, 2001;Lee et al, 1999;Malik et al, 1992;Ragoowansi and Piepgras, 1991). Our case is an example of the latter-a leptomeningeal metastasis opposite the side of the craniotomy that presented 2 years after removal of the primary tumor.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Either tumor may be cystic, solid, or both (Burger et al, 1994). Despite their benign histology, craniopharyngiomas may rarely recur as a result of implantation along the operative tract or as remote deposits or metastases due to cerebrospinal uid spread (Barloon et al, 1988;Gupta et al, 1999;Israel and Pomeranz, 1995;Ito et al, 2001;Lee et al, 1999;Malik et al, 1992;Ragoowansi and Piepgras, 1991). Our case is an example of the latter-a leptomeningeal metastasis opposite the side of the craniotomy that presented 2 years after removal of the primary tumor.…”
mentioning
confidence: 76%
“…The literature cites only 5 "ectopic" recurrences, all along the tract of the surgical route and presumably the result of operative implantation (Barloon et al, 1988;Israel and Pomeranz, 1995;Lee et al, 1999;Ragoowansi and Piepgras, 1991). An epidural craniopharyngioma recurrence, physically separate from the primary site but ipsilateral to the cran-iotomy, has also been reported (Malik et al, 1992). The authors rightly suggested that a piece of tumor may have been displaced during surgery and subsequently grew (Malik et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11]13,14,16) The nine male and six female patients were aged 2 to 73 years (mean 36.3 years). The primary craniopharyngioma was located in the suprasellar region in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy was performed in two cases. 1,11) The time between the initial operation and ectopic recurrence ranged from 6 months to 21 years (mean 4.9 years). The most common region of ectopic recurrence was the frontal lobe convexity in nine cases, with one case in the epidural space of the frontal region, 7) and one case in the intradural extramedullary region of the lumbar spinal cord.…”
Section: Discussionmentioning
confidence: 99%